Monitoring the film formation process of polystyrene/poly acrylamide (PS/PAAm) composite films annealed by IR heating - Gelir, Ali; Yargi, Onder; Sarli, Berkay; Sahinturk, Utkan; Aksakal, Baki (WILEY, 2018)
In this study, UV-visible (UVV) technique was used to probe the evolution of optical transmission during the film formation from composites of polystyrene (PS) latex particles and poly acrylamide (PAAm) films annealed by the infrared radiative heating (IRH) and convectional heating. Activation energies corresponding to the void closure and the interdiffusion stages were calculated. It was shown that the activation energy for the void closure processes of viscous flow from the composite films decreased considerably in IRH annealing technique. It was observed that IRH heating speeds up the film formation process and the decrease the required energy. POLYM. ENG. SCI., 58:353-360, 2018. (c) 2017 Society of Plastics Engineers
Keywords: GLASS-TRANSITION TEMPERATURE; PHOTON TRANSMISSION; LATEX-PARTICLES; MOLECULAR-WEIGHT; CARBON NANOTUBE; FLUORESCENCE; INTERDIFFUSION; DEFORMATION; DISPERSION; KINETICS; Engineering; Polymer Science